Aplikasi Perbandingan Pemilihan Guru Private Homeschooling menggunakan Algoritma Simple Additive Weighting (SAW) dan Weight Product Berbasis Web - Setiawan, Raka Adji; Fauziah, Fauziah; Komala Sari, Ratih Titi (KITA Institut, 2021)
This study aims to compare the selection of private homeschool teachers using the Simple Additive Weighting (SAW) and Weight Product (WP) algorithms, the criteria that have been taken by the author to calculate their weight in selecting private teachers who excel and provide convenience with an assessment based on criteria. In this effort, the authors can build a private teacher selection system with the Simple Additive Weighting (SAW) algorithm to find the total weights of the teacher performance rating for each alternative on all attributes and compare it to the Weight Product (WP) algorithm using the multiplication technique to link the attribute rating. where the attribute type rating must be ranked first with the associated weight attribute. From the results of this study, the authors have described how the design and application of SAW and WP in making a Decision Support System in selecting private homeschooling teachers.Keywords:Simple Additive Weighting (SAW), Weight Product (WP), Decision Support Systems, Teacher Selection, Homeschooling.